PROSEDUR PENERAPAN APLIKASI SRIKANDI 2.0 INSTANSI PEMERINTAH - Almakara Khalishah (2023)
The Srikandi application is one of the important innovations in the context of government that aims to improve operational effectiveness, data accessibility, public services and simplify the process of distributing letters through electronic media. The research methods used include observation, documentation, data analysis and interviews with relevant stakeholders. The results showed that the use of the Srikandi App had a positive impact. There is a significant improvement in customer service efficiency and productivity with reduced response time and faster handling of customer inquiries and requests. In addition, the use of this application has also reduced the operational costs of government agencies related to customer service, as simple and routine tasks can be handled automatically by the application.